Pengaruh Penerapan Green Accounting Terhadap Kinerja Keuangan Perusahaan Manufaktur Subsektor Industri Makanan Dan Minuman Yang Terdaftar Di Bei - Kamiline Mahaballah Uzla; Nawangsari, Ajeng Tita (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This The purpose of this study is to determine the impact of green accounting on a company's financial performance. The population in this study is companies in the manufacturing sector, specifically the food and beverage industry, that are listed on the Indonesia Stock Exchange from 2021 to 2023. The research method used is a quantitative approach with secondary data in the form of company annual reports. The sample was selected using purposive sampling with three criteria, resulting in six companies that were deemed suitable for research. The study used simple regression analysis with the SPSS program. In this study, the green accounting variable was measured using PROPER ranking values, and the financial performance variable was measured using ROA. The results of the analysis show that the green accounting variable does not significantly affect the company's financial performance.